Women Empowerment in Little Mix's â€œSaluteâ€: Feminist Stylistic Analysis - Artanti, Chairinnisa; Zulaika, Adristi Yajna; Rangkuti, Rahmadsyah (Titian: Jurnal Ilmu Humaniora, 2023)
This study conducts a feminist stylistic analysis of Little Mix's song "Salute" within the theoretical framework proposed by Sara Mills. Utilizing Mills's three-level structure outlined in "Feminist Stylistics", the study employs a descriptive-qualitative methodology inspired by Creswell's theory. The primary focus is to explore the representation of women's empowerment in the song. Analysis occurs at the levels of word, phrase/sentence, and discourse, connecting linguistic choices to feminist themes. The word-level analysis uncovers generic pronouns and nouns such as "you," "we," "ladies," "women," "sisters," "warriors," and "queens," emphasizing a collective female identity. At the phrase level, nine metaphors and three transitivity processes (material, mental, and relational) highlight the multifaceted aspects of empowerment. Discourse-level analysis reveals characterization and focalization, providing deeper insights into the characters' perspectives in the song. Overall, the linguistic choices in the song, as identified through the three-level analysis, consistently align with feminist principles, emphasizing women's empowerment as a central theme. Abstrak Penelitian ini melakukan analisis gaya feminis terhadap lagu "Salute" oleh Little Mix dalam kerangka teoritis yang diusulkan oleh Sara Mills. Dengan menggunakan struktur tiga tingkat Mills yang diuraikan dalam "Feminist Stylistics", penelitian ini mengadopsi metodologi deskriptif-kualitatif yang terinspirasi oleh teori Creswell. Fokus utamanya adalah untuk mengeksplorasi representasi pemberdayaan perempuan dalam lagu tersebut. Analisis dilakukan pada tingkat kata, frasa/kalimat, dan wacana, menghubungkan pilihan linguistik dengan tema feminis. Analisis tingkat kata mengungkapkan kata ganti dan kata benda generik seperti "you," "we," "ladies," "women," "sisters," "warriors," dan "queens," menekankan identitas perempuan kolektif. Pada tingkat frasa, sembilan metafora dan tiga proses transitivitas (material, mental, dan relasional) menyoroti berbagai aspek pemberdayaan perempuan. Analisis tingkat wacana mengungkapkan karakterisasi dan fokalisasi, memberikan wawasan lebih mendalam ke dalam perspektif karakter dalam lagu. Secara keseluruhan, pilihan linguistik dalam lagu, seperti yang diidentifikasi melalui analisis tiga tingkat, secara konsisten sejalan dengan prinsip feminis, menekankan pemberdayaan perempuan sebagai tema utama.